Sarcoma de Kaposi em membros inferiores: relato de caso - Kalil, Jorge Agle (2010)
The Kaposi sarcoma is an angio-proliferative malignant neoplasm that mostly affects the skin and subcutaneous tissue, although it can present in a more aggressive form, involving the oral cavity, lungs and gastrointestinal tract (visceral Kaposi sarcoma). It is classified into 4 clinical-epidemiological types: classic, endemic, iatrogenic and epidemic, all of them associated with the human herpesvirus 8. We report a rare case of Kaposi sarcoma in an elderly immunodepressed female patient, not related to the acquired immunodeficiency syndrome, that evolved fatally in five months, since the appearance of hematic necrotic bullous lesions which progressed with intense local exudation, dehydration, renal insufficiency and worsening of the clinical status, ending in death, caused by multiple organ failure.